2019
DOI: 10.1016/j.xkme.2018.12.003
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Repository Corticotropin Gel (Acthar) in Progressive Nephrotic Syndrome Secondary to Transplant Glomerulopathy: A Report of Three Cases

Abstract: Transplant glomerulopathy is a feared complication of kidney transplantation, often resulting in rapid loss of kidney function and ultimate graft failure. The underlying cause is unclear, with both antibody and cellmediated immune mechanisms postulated, as well as intrinsic glomerular factors. At the present time, there is no known therapy. We report here 3 cases in which corticotropin gel (Acthar) was used with varying response of proteinuria and stabilization of graft function with continued graft survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In an analysis of 14 patients with recurrent FSGS from 2 transplant centers, patients received ACTH therapy for 6 months to 2 years with an overall response rate of 36% without adverse events 20 . Besides, previous studies have indicated that ACTH has a certain effect on the recurrent FSGS resistant to conventional therapy 2,3,6,21–23 . The urinary protein of this patient in our center decreased significantly after 1 year of ACTH treatment and was maintained at 0.6~1.1 g/m 2 /day.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In an analysis of 14 patients with recurrent FSGS from 2 transplant centers, patients received ACTH therapy for 6 months to 2 years with an overall response rate of 36% without adverse events 20 . Besides, previous studies have indicated that ACTH has a certain effect on the recurrent FSGS resistant to conventional therapy 2,3,6,21–23 . The urinary protein of this patient in our center decreased significantly after 1 year of ACTH treatment and was maintained at 0.6~1.1 g/m 2 /day.…”
Section: Discussionmentioning
confidence: 69%
“…20 Besides, previous studies have indicated that ACTH has a certain effect on the recurrent FSGS resistant to conventional therapy. 2,3,6,[21][22][23] The urinary protein of this patient in our center decreased significantly after 1 year of ACTH treatment and was maintained at 0.6~1.1 g/m 2 /day. After 568 days of ACTH treatment, the urinary protein decreased below 0.5 g/m 2 /day and was maintained until now.…”
Section: F I G U R E 3 Renal Function After Using Acthmentioning
confidence: 64%
“…However, responses are wide, and further research is needed to identify those patients who are benefitted by rituximab treatment and those who are non-effective. A clinical study showed that adrenocorticotropic hormone exerted its role through activated melanocortin receptors (MC1R–MC5R) that existed in the whole body were effective therapy for IMN patients who failed immunosuppressive treatment ( Markell et al, 2019 ; Wu et al, 2021b ). Melanocortin one receptor occurred in B cells, T cells, podocytes, and antigen-presenting cells.…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 99%
“…A single center report described the potential benefit of Acthar gel in TG 63 . Further controlled trials are required to test its use in TG.…”
Section: Treatmentmentioning
confidence: 99%